THE VIOLATION OF CONVERSATIONAL MAXIMS FOUND IN POLITICAL CONVERSATION AT ROSI TALKSHOW - Sri Septela Rahmi; Refnaldi Refnaldi; Delvi Wahyuni (English Language and Literature, 2018)
This study focuses on cooperative principle violation done by the interviewee in answering the question in Rosi Talkshow at Kompas TV using Grice’s theory. The objectives of study are to discover the type of conversational maxim violation and the reason the interviewee violate the maxims in talk show. The data is utterances between the interviewer and the interviewee taken from internet. This research was conducted by using descriptive method. The results of the study show that there are four maxims of the cooperative principle violated by the interviewee in answering the question at Rosi Talkshow. These maxims are: (1) maxim of quality (2) maxim of quantity, (3) maxim of relation, and (4) maxim of manner. The dominant maxim that is violated is maxim of quantity which occurred 18 times, whereas the other maxim such as maxim of relation occurred 14 times, maxim of quality 9 times and maxim of manner only occurred 6 times. The most dominant type of maxim violation is quantity because the speakers give information as much as possible to make it clear and to create good image with good words to get sympathy from audiences.